Self-consistent modelling of the Milky Way’s nuclear stellar disc - Sormani, Mattia C.; Sanders, Jason L; Fritz, Tobias K; Smith, Leigh C; Gerhard, Ortwin; Schödel, Rainer; Magorrian, John; Neumayer, Nadine; Nogueras-Lara, Francisco; Feldmeier-Krause, Anja; Mastrobuono-Battisti, Alessandra; Schultheis, Mathias; et al. (Monthly notices of the Royal Astronomical Society, 2022)
The nuclear stellar disc (NSD) is a flattened high-density stellar structure that dominates the gravitational field of the Milky Way at Galactocentric radius $30\, {\rm pc}\lesssim R\lesssim 300\, {\rm pc}$. We construct axisymmetric self-consistent equilibrium dynamical models of the NSD in which the distribution function is an analytic function of the action variables. We fit the models to the normalized kinematic distributions (line-of-sight velocities + VIRAC2 proper motions) of stars in the NSD survey of Fritz et al., taking the foreground contamination due to the Galactic Bar explicitly into account using an N-body model. The posterior marginalized probability distributions give a total mass of $M_{\rm NSD} = 10.5^{+1.1}_{-1.0} × 10^8 \, \, \rm M_\odot$, roughly exponential radial and vertical scale lengths of $R_{\rm disc} = 88.6^{+9.2}_{-6.9} \, {\rm pc}$ and $H_{\rm disc}=28.4^{+5.5}_{-5.5} \, {\rm pc}$, respectively, and a velocity dispersion $σ \simeq 70\, {\rm km\, s^{-1}}$ that decreases with radius. We find that the assumption that the NSD is axisymmetric provides a good representation of the data. We quantify contamination from the Galactic Bar in the sample, which is substantial in most observed fields. Our models provide the full 6D (position + velocity) distribution function of the NSD, which can be used to generate predictions for future surveys. We make the models publicly available as part of the software package agama.
Gesehen am 22.04.2022